The evaluation of safety and efficacy of percutaneous nephrostomy in young adult patients with severe hydronephrosis due to uretropelvic junction obstructions - Chandra, Mahesh; Bachches, Nikhil; Bhattacharya, Anish; Attri, Ashok (International Journal of Research in Medical Sciences, 2019)
Background: Majority of poorly functioning kidney (PFK) due to primary ureteropelvic junction obstructions (UPJO) in young adult have potential to recover after an attempted percutaneous nephrostomy (PCN). The split renal function measured by nuclear renal scan may not be sufficient enough to predict recovery of such kidney. Therefore, this study was undertaken to determine the functional recovery and potential salvageability of PFK due UPJO. Objective of the study was to evaluate safety and efficacy of PCN in adult patients with severe hydronephrosis due to PUJO. Methods: A total of 25 (10 male and 15 female) young adult patients of severe hydronephrosis due to PUJO and SRF<20% underwent PCN procedures. Only, those who had significant improvement in their SRF ≥10% and developed PCN output ≥400 ml/day underwent Anderson-Hyenas pyeloplasty and rest underwent nephrectomy. Results: Both male and female young patients had significantly improvement after 6 weeks of PCN, their mean pre-PCN SRF changed from 16.30% and 12.27% to became 28.10±08.41% and 18.53±09.89%, respectively. Those with age <30 years improved most with ≥10% increase in the mean SRF and in 72% patients average PCN output increased from 279.80±93.90 ml/day to 445.20±160.341 ml/day at 6 weeks period. Overall, the patients with average PCN output ≥400 ml/day had a mean improvement of 10.33±05.48% in SRF. However, 5(20%) developed haematuria, 8% fever, 16% displaced PCN tip with no major puncture site bleed. Conclusions: The trial of PCN before definite surgery in young adult patients with poorly functioning kidney due to UPJO not only predicts renal renal function recovery but also prevent unwarranted renal loss.